Mean difference in timing of first antenatal checks across regions and associated factors among pregnant women attending health facilities in Ethiopia: evidence from Ethiopian demographic health survey, 2019 - Gemechu Chemeda Feyisa; Alemayehu Dagne; Delelegn Woyessa; Tenna Ephrem; Ausman Ahmed; Habtamu G/Senbet; Getachew Chane; Senahara Korsa Wake (BMC, 2023)
Abstract Introduction Early initiation of antenatal care visits is an essential component of services to improve maternal health. Conducting a detailed study about the mean difference in timing at first antenatal checks across regions and factors associated with timing at first antenatal checks among women attending antenatal in Ethiopia is essential to ensure maternal and newborn health. Therefore, this study aimed to describe the mean difference in timing at first antenatal visits and associated factors among pregnant women attending different health facilities across regions in Ethiopia. Method The Ethiopian Demographic and Health Survey (EDHS) conducted a community-based cross-sectional study in 2019. In this study, data about the timing of the first antenatal check-ups were requested from the Demographic Health Survey in February 2023, and the required variables were downloaded in SAS and SPSS formats from the data set. A total of 2935 women from nine regional states and two city administrations with an age range of 15 to 49 years were included in the study. The mean difference in timing at first antenatal check-ups, its correlation and various factors were estimated using multiple linear regressions to identify factors. Result The majority of the 2034 (69.3%) of pregnant women who participated in the study were rural residents. The mean (± SD) age of the pregnant women was 29 (± 6.5) years. Approximately 32.5% of pregnant women visited their first antenatal check after 4 months of pregnancy. The results showed that counselling by health workers during a previous pregnancy (p < 0.01) significantly predicts timing at first antenatal checks in months holding previous delivery, previous antenatal care at both government and private facilities, ever attended school, and highest educational level. Timing at the first antenatal check-in months is expected to decrease by 0.99 months for every counselling session at each pregnancy. The results of the analysis suggested that the regression model significantly predicted timing at the first antenatal check (p = 0.001). Conclusion The mean difference in timing at the first antenatal check in months among Ethiopian pregnant women relatively significantly varies in two regions. Previous pregnancy counselling by health workers positively influences the timing of first antenatal check-ups for subsequent antenatal check follow-ups in Ethiopia.